Structural and emission properties of Tb3+-doped nitrogen-rich silicon oxynitride films. (17th February 2017) - Labbé, C; An, Y-T; Zatryb, G; Portier, X; Podhorodecki, A; Marie, P; Frilay, C; Cardin, J; Gourbilleau, F
Abstract: Terbium doped silicon oxynitride host matrix is suitable for various applications such as light emitters compatible with CMOS technology or frequency converter systems for photovoltaic cells. In this study, amorphous Tb 3+ ion doped nitrogen-rich silicon oxynitride (NRSON) thin films were fabricated using a reactive magnetron co-sputtering method, with various N2 flows and annealing conditions, in order to study their structural and emission properties. Rutherford backscattering (RBS) measurements and refractive index values confirmed the silicon oxynitride nature of the films. An electron microscopy analysis conducted for different annealing temperatures ( T A ) was also performed up to 1200 °C. Transmission electron microscopy (TEM) images revealed two different sublayers. The top layer showed porosities coming from a degassing of oxygen during deposition and annealing, while in the region close to the substrate, a multilayer-like structure of SiO2 and Si3 N4 phases appeared, involving a spinodal decomposition. Upon a 1200 °C annealing treatment, a significant density of Tb clusters was detected, indicating a higher thermal threshold of rare earth (RE) clusterization in comparison to the silicon oxide matrix. With an opposite variation of the N2 flow during the deposition, the nitrogen excess parameter (Nex ) estimated by RBS measurements was introduced to investigate the Fourier transform infrared (FTIR) spectrum behavior and emission properties. Different vibration modes of the Si–N and Si–O bonds have been carefully identified from the FTIR spectra characterizing such host matrices, especially the 'out-of-phase' stretching vibration mode of the Si–O bond. The highest Tb 3+ photoluminescence (PL) intensity was obtained by optimizing the N incorporation and the annealing conditions. In addition, according to these conditions, the integrated PL intensity variation confirmed that the silicon nitride-based host matrix had a higher thermal threshold of rare earth clusterization than its silicon oxide counterpart. Analysis of time-resolved PL intensity versus T A showed the impact of Tb clustering on decay times, in agreement with the TEM observations. Finally, PL and PL excitation (PLE) experiments and comparison of the related spectra between undoped and Tb-doped samples were carried out to investigate the impact of the band tails on the excitation mechanism of Tb 3+ ions.